Penerapan Pidana Tambahan Berupa Uang Pengganti Dalam Perkara Tindak Pidana Korupsi - Muammar, Muammar; Meldandy, Maulana (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
The determination of additional punishment in the form of "replacement money" should ideally be equal or balanced with state financial losses as a result of criminal acts of corruption. Interesting in the decision of the Semarang District Court Number: 32/Pid.Sus/2012/PN.Tipikor.smg there is an unequal determination of "replacement money" when compared to state financial losses resulting from criminal acts of corruption committed by the defendant in the "Budget" corruption case. Maintenance of Motorized Service Vehicles by the Chairperson of the Grobogan Regency DPRD for the 2009-2014 periodâ€. The research used in this research is normative legal research with a conceptual approach. In the approach to legislation (Statute Approach), the author describes the hierarchy, and the principles in the legislation. In addition, in this study the author uses aspects of a conceptual approach (Conceptual Approach), where the author tries to describe the concept of law by moving from the views of legal experts. In this study, it was found that regarding the legality of additional criminal charges in the form of replacement money in corruption cases, it is found in Article 18 paragraph (1) letter b of Law no. 31 of 1999 concerning the Crime of Corruption, namely "payment of compensation as much as possible equal to the property obtained from the crime of corruption". The judge's consideration in the decision above is concluded to be less relevant if it is associated with additional penalties in the verdict in the form of replacement money.Keywords: Corruption, Additional Criminal, Compensation Money